The role of amorphous precursor in phase selection hierarchy in marginal metallic glasses. (15th December 2016) - Yildirim, C.; Kutsal, M.; Ott, R.T.; Besser, M.F.; Kramer, M.J.; Kalay, Y.E.
Abstract: The solid state amorphous structure and devitrification products of Al90 Tb10 alloys produced by Cu block melt-spinning and magnetron sputtering were investigated by a combined study of differential scanning calorimetry, in-situ X-ray diffraction and conventional transmission electron microscopy. The as-prepared specimens were found to be fully amorphous according to the electron and X-ray diffraction. The thermal analysis and in-situ XRD analyses of the amorphous samples having the same chemistry but different processing history showed clear differences in the devitrification pathways in terms of nanocrystal population, size and the phase selection. The variations in the crystallization path were explained on the basis of distinct topological and chemical medium range ordering observed in as-quenched and as-sputtered amorphous structures. Graphical abstract: Highlights: Different MRO structure were detected in metallic glasses produced using different techniques. Metallic glasses having the same chemistry devitrifies to different crystals. High number density of nanocrystals are formed by subsequent devitrification of metallic glasses.